Country risk in foreign direct investment: similarities and differences with country risk in exports - Dans Rodríguez, Noemi (Nómadas. Critical Journal of Social and Juridical Sciences, 2016)
Country Risk in exports is derived from the capacity of payment and the losses that insolvency can cause to the creditors. Instead, the country risk in foreign direct investment is related to breach of contract, deprivation of property rights, damage to assets or cessation of activities. The operations of foreign direct investment (FDI) are different in nature to exports. Therefore, regarding country risks some questions arise: is country risk different also?, which are the common risks and which are specific risks to exports and FDI? Both share five types of country risk: the transfer risk, the impossibility of converting currencies, the exchange rate risk, the risk of war or political violence and sovereign risk. The risk of expropriation is specific to foreign direct investment and does not affect trade. This paper makes a comparative analysis of the risks in exports and foreign direct investment. The aim is to find out to what extent they differ. The conclusions are valid for multinational firms and developing countries with a growth strategy based on FDI.